Effect of stocking density on growth, survival and feed utilization of Labeo rohita reared in cage in a tropical reservoir - Swain, H. S.; Upadhyay, A.; Ramteke, M. H.; Meena, D. K.; Sarkar, U. K.; Sahoo, A. K.; Chadha, N. K.; Rawat, K. D.; Das, B. K. (Journal of the Inland Fisheries Society of India, 2022)
Labeo rohita (30.35±1.08 g) was reared in cages for 240 days at three stocking densities, viz., 10 nos.m-3 (R10), 20 nos.m-3 (R20), and 30 nos.m-3 (R30) in triplicates at Salia reservoir, Odisha, India. The fishes were fed with commercial floating pellet feed (CP: 28%, CL: 4%) @ 5-3% of the body weight. L. rohita stocked @10 nos. m-3 showed a significantly higher (P<0.05) final body weight (680.69±21.30g) and weight gain (650.34±21.30g) among the three stocking densities. Specific growth rate (SGR) did not significantly differ (P>0.05) between R10 and R20, however, survival (%) was different at different stocking densities (P<0.05). The highest protein efficiency ratio (1.69±0.01) was observed at 10 nos.m-3 and lowest at 30 nos.m-3. The production (kg m-3) was 5.98 ± 0.53, 8.06 ± 0.71 and 8.05 ± 1.13 in R10, R20 and R30 respectively, however, the benefit-cost (B/C) ratio was found higher at R10. The growth performances and B/C ratio suggest that the stocking density of advance fingerling of rohu at 10 nos.m-3 in cages in tropical reservoirs of India is suitable for grow-out production. Keywords Carp; Labeo rohita; Cage; performance; growth